The accuration of Nur Murtaji Mosque qibla direction at Bintan Regency Riau Islands Province - Angkat, M. Arbisora (Penerbit Universiti Kebangsaan Malaysia, 2023)
From 2019 until 2020, 30 calibrations of the qibla direction of mosques in Bintan Regency have been calibrated. In 2021, the author also carried out three calibrations of the qibla direction of mosques in Bintan Regency and Tanjungpinang City. From three activities for calibrating the mosque’s qibla direction, there was one mosque that deviated slightly from the qibla direction, because the construction of the mosque used a smartphone compass application in determining the qibla direction. The calibration of the qibla direction occured due to the lack of knowledge from the mosque residents about the qibla direction, like about how to measure the qibla direction and tools that become the standard in measuring the qibla direction. Because there is a lot of qibla direction calibration, the author calibrated the Nur Murtaji Mosque qibla direction to determine the accuracy of Nur Murtaji Mosque qibla direction. This study used comparative analysis techniques, namely by comparing the previous and the current measurement of Nur Murtaji Mosque qibla direction. From the calculations, it was known that the qibla direction was 2930 02’ 48.06” NESW (North-East-South-West). The qibla direction of the Nur Murtaji Mosque was accurate because there was no deviation that occurred after comparison.